The poly‐extreme tolerant black yeasts are prevalent under high ultraviolet light and climatic seasonality across soils of global biomes. (24th March 2022) - Coleine, Claudia; Selbmann, Laura; Singh, Brajesh K.; Delgado‐Baquerizo, Manuel
Summary: Black yeasts are among the most stress‐tolerant organisms of the planet, thriving under all types of terrestrial habitats and extreme environments. Yet, their global patterns and ecology remain far less studied, limiting our capacity to identify the main environmental drivers of these important organisms across biomes. To fill this knowledge gap, we analysed topsoils from 235 terrestrial ecosystems across and within globally distributed climate groups (i.e. dry, temperate and continental). We found that soils are important repositories of black yeasts, and that ultraviolet light, fine soil texture, and precipitation seasonality are the most consistent environmental factors associated with their diversity across biomes. Finally, we identified Exophiala and Cladophialophora as the most dominant black yeasts genera in soils across the globe. These findings provide novel evidence of global distribution of black yeasts and their key environmental predictors, giving new insights for speculating the evolution and spreading of these extreme‐tolerant organisms throughout both natural and human associated extreme environments.